PERBEDAAN TINGKAT STRES AKADEMIK MAHASISWA SEMESTER AWAL DAN SEMESTER AKHIR DI FKIP UPI YPTK PADANG - Asnatul Hadijah, Wina; Ridho Rismi; Mufadhal Barseli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic stress is a psychological condition commonly experienced by university students due to academic demands and developmental challenges during higher education. Differences in semester levels may influence stress intensity because students encounter distinct academic responsibilities and expectations. This study aimed to determine whether there is a significant difference in academic stress levels between first-semester and final-semester students at FKIP UPI YPTK Padang. This research used a quantitative comparative design with purposive sampling involving 72 students consisting of 36 first-semester and 36 final-semester students. Data were collected using a Likert-scale academic stress questionnaire. Data analysis included normality test, homogeneity test, and independent sample t-test using SPSS. The results showed a significance value (2-tailed) of 0.502 > 0.05, indicating no significant difference between the two groups. These findings suggest that academic stress may occur across academic levels and highlight the importance of comprehensive counseling services in higher education institutions.